THE EFFECT OF GIVING FOOT MASSAGE THERAPY ON ANXIETY LEVELS IN CHRONIC KIDNEY FAILURE PATIENTS - Wijaya, Leni; Purnama Dewi, Bela (Rifapublisher.id, 2025)
Background: One of the therapies for CKD patients is hemodialysis (HD), but the HD procedure requires a long and periodic time which can cause physiological and psychological problems experienced by patients such as fatigue, anxiety and sleep disorders. One of the non-pharmacological treatments to overcome anxiety is foot massage therapy. The purpose: of this study was to determine the effect of providing Foot Massage therapy on anxiety levels in chronic kidney failure patients in the hemodialysis room of Pertamina Hospital Palembang. Method: The research method used in this study was pre-experimental with a one group pre-test and post-test design approach. The population in this study were all hemodialysis patients at Pertamina Hospital Palembang as many as 20 people. The sampling technique used total sampling with a sample of 20 respondents. Data collection used a questionnaire sheet. Data analysis used univariate and bivariate analysis using the Paired Sample T Test. Results: The study showed that before Foot Massage therapy, 10 respondents (50%) experienced mild anxiety and after Foot Massage therapy, 8 respondents (40%) did not experience anxiety. The results of the Paired Sample t Test obtained a p value = 0.000, which means that there is an effect of providing Foot Massage therapy on the level of anxiety in chronic kidney failure patients in the hemodialysis room of Pertamina Hospital Palembang in 2024. It is hoped that it can help hemodialysis patients to reduce anxiety levels by providing foot massage therapy as one of the ongoing therapies to be carried out or interpreted in reducing anxiety in the hemodialysis room of Pertamina Hospital Palembang.